How to solve this limit \lim_{x\to pi/4} (sin2x)^(tan^2(2x)) ?

2 Answers
Mar 2, 2018

1/sqrt(e)

Explanation:

you can Look at this link for Reference https://math.oregonstate.edu/home/programs/undergrad/CalculusQuestStudyGuides/SandS/lHopital/power_limits.html

The trick here is to use L'Hopital's Rule. although you might say there are no fractions but we can convert them into it. here is the start of my solution

And I want to clarify, I will be using the variable which you used as y and not x and use x as equal to 2y

therefore your question is
lim _(y -> pi/4) (sin(2y))^(tan^2(2y))

to simplify,
let x be 2y
Realize that the equation is equal to

lim _(x-> pi/2) (sin(x))^(tan^2(x))

as When y approaches pi/4, x approaches pi/2 as x = 2y

Now, Break this up into an exponential with the base e

therefore,

lim _(x-> pi/2) e^(tan^2(x) * ln(sin(x))
using exponential rules

now, Bring the limit inside the equation using the Composition Law
https://math.oregonstate.edu/home/programs/undergrad/CalculusQuestStudyGuides/SandS/lHopital/limit_laws.html#Composition_Law

therefore the above equation is equal to
e^( lim _(x-> pi/2) tan^2(x) * ln(sin(x))

Now Lets just focus on the Limit and try to use L'hôpital's Rule on it, but first, we need to convert it into a division of two functions

therefore,
lim _(x-> pi/2) tan^2(x) * ln(sin(x))
=
lim _(x-> pi/2) ln(sin(x))/(1/tan^2(x))

I assume you already know how to take the derivative of the two functions ln(sin(x)) and 1/tan^2(x) which comes out as

(d/dx ln(sin(x))) / (d/dx 1/tan^2(x)

= cot (x)/ (-2 cot (x)*csc^2 (x))

after cancelling cot (x), we Get
= 1/ (-2 *csc^2 (x))

therefore the limit is
lim _(x-> pi/2) 1/ (-2 *csc^2 (x))

which is continuous and defined at x = pi/2 and csc^2(pi/2) is 1, therefore the entire power becomes 1/-2 = - 1/2

and don't forget, this is the power e is raised to so the Complete limit is e^(-1/2)
=
1/sqrt(e)

Mar 2, 2018

1/sqrte

Explanation:

Making y = pi/4-x

sin(2x)^(tan^2(2x))=sin(pi/2-2y)^(tan^2(pi/2-2y)) = cos(2y)^(cot^2(2y)

now x->pi/4 rArr y -> 0 and then making z = 2y

lim_(x->pi/4)sin(2x)^(tan^2(2x)) equiv lim_(z->0)(cosz)^(cot^2z)

but cot^2 z = 1/sin^2z - 1 = 1/(1/2(1-cos(2z)))-1 then

(cosz)^(cot^2z) = (cos z)^(2/(1-cos(2z)))/cosz

but 2/(1-cos(2z)) = 1/(1-cos^2z) = 1/2(1/(1-cosz)-1/(1+cosz))

then

lim_(z->0)(cosz)^(cot^2z) = lim_(z->0)(cosz)^(1/2(1/(1-cosz)-1/(1+cosz)))/cosz =

lim_(z->0)(cosz)^(1/2(1/(1-cosz)))/(cosz)^(1/2(1/(1+cosz))) 1/cosz =

=lim_(z->0)(cosz)^(1/2(1/(1-cosz)))

because

lim_(z->0)1/(cosz (cosz)^(1/2(1/(1+cosz)))) = 1

Now expanding cosz = 1-1/2 z^2 + O(z^4) near the origin we have

lim_(z->0)(cosz)^(1/2(1/(1-cosz))) equiv lim_(z->0) (1-z^2/2+O(z^4))^(1/2(1/(z^2/2 - O(z^4)))) = sqrt(lim_(z->0) (1-z^2/2+O(z^4))^(1/(z^2/2 - O(z^4))))=1/sqrte